Experimental and comparative modeling study of high temperature and very high pressure methylcyclohexane pyrolysis. (1st February 2019) - Liszka, Miroslaw Krzysztof; Brezinsky, Kenneth
Abstract: Three sets totaling 118 individual methylcyclohexane shock tube pyrolysis experiments were completed at nominal pressures of 40, 100, and 200 bar to obtain species data and to determine whether the formation of alkylcyclopentanes, which have been found to be sooting and coking precursors in previous studies conducted in the supercritical phase, is possible at high pressures but dilute conditions. Some species profiles, namely ethane, propadiene, propyne, 1-butene, and toluene were affected by the experimental variation in pressure, but no alkylcyclopentanes were observed to form. An additional set comprised of 33 individual experiments was completed at 40 bar to match the concentration of the fuel present in the reflected shock reaction zone present in the 100 bar experiments. The species data obtained from the additional set of 40 bar experiments reproduced the 100 bar data nearly perfectly, emphasizing the dominance of the initial fuel concentration rather than pressure over the product distribution at the experimental conditions present in this study. The experimental data were also compared against simulations with a recently published methylcyclohexane mechanism and a generated mechanism with both mechanisms being able to predict the formation of major product species well. The generated mechanism is able to capture the current data better than the literature mechanism and is recommended for use at conditions similar to those in the present study, but requires larger computational effort and time and only contains pyrolysis reactions.